GENDER DIVERSITY, INCLUSION AND PROMOTION TO LEADERSHIP POSITION IN HIGHER EDUCATION ADMINISTRATION IN INDIA - Dr.Padma Misra, Rakhi Kumari (International Journal of Advanced Science and Technology, 2020)
The women’s role in leadership positions is an escalating extensive topic for both Academic institutions, business organisations and Industries. Even though the idiom gender diversity & inclusion has got ample attention in institutions and industries, there still remains little women’s presence in higher or top administrative positions. Despite having women friendly image of higher education sector in India it still continues to be male dominant sector.